Typing as a Practical Life Skill to Improve Writing Efficacy in the Secondary Montessori Classroom - Richardson, Anne (My University, 2017)
In a world where typing is still the main form of electronic communication, students at an urban Montessori public middle school do not receive formal typing training. This study was designed to examine the effects of online typing classes as a practical life exercise in the Montessori secondary classroom on writing quality, quantity, and self-efficacy. First the students took a survey to determine their behavior toward writing and their typing speed in Words per Minute (WPM). Then they signed up for an online typing course through which the action researcher could analyze each student’s progress. Students were able to practice their typing skills as one of their choices during the work cycle. After 4 weeks, the researcher administered another survey to determine changes in WPM and attitudes toward writing and typing. Results showed that most students improved their writing quantity and displayed positive writing behaviors because of their gained knowledge on the keyboard. Additionally, students who struggled to work without the help or supervision of a teacher showed growth toward independent learning.